ChemInform Abstract: Synthesis and Characterization of Frustrated Spin Ladders SrFe2S2O and SrFe2Se2O. Issue 35 (September 2015) - Huh, Sungjoon; Prots, Yurii; Adler, Peter; Tjeng, Liu Hao; Valldor, Martin
Abstract Single crystals and polycrystalline samples of SrFe2S2O (I) and SrFe2Se2O (II) are prepared by solid state reaction of stoichiometric amounts of SrO, Fe, and S (Se) (evacuated quartz tubes, 800 °C, 30 h; 3 (I) and 5 (II) repetitions of the heating schedule).